Enhanced Ad Hoc On-Demand Distance Vector Routing Protocol For Mobile Ad Hoc Network Internet Connectivity - Gurusamy, Gobi (2006)
An ad hoc network is a collection of wireless mobile nodes dynamically forming a temporary network without the use of any existing network infrastructure or centralized administration and consists of mobile nodes that use a wireless interface to communicate with each other. These mobile nodes serve as both hosts and routers so they can forward packets on behalf of each other. Hence, the mobile nodes are able to communicate beyond their transmission range by supporting multi hop communication. However, the fact that there is no central infrastructure and that the devices which can move randomly gives rise to various kinds of problems, such as routing and security and quality of service (QoS). In this thesis the problem of routing is considered. An Ad-Hoc network has certain characteristics, which impose new demand on the routing protocol the most important characteristic is the dynamic topology, which is a consequence of node mobility. Nodes can changes position quite frequently, which means that we need a routing protocol that quickly adapts to topology changes. The nodes in ad hoc network can consist of laptops and PDA (Personal Digital Assistants) and are often very limited in resources such as CPU capacity, storage capacity, battery power and bandwidth. This means that routing protocol should try to minimize control traffic, such as period update message. Instead the routing protocol should be reactive, thus only calculate routes upon receiving a specific request. The Internet Engineering Task Force (IEFT) currently has a working group called mobile Ad hoc network (MANET) that is working on routing specification for Ad hoc networks. This thesis evaluates some of the routing protocols such as AODV (Ad hoc on demand Distance vector) and DSR (Dynamic Sources Routing) and DSDV (Destination Sequenced Distance vector) for performance testing and an enhanced implementation of AODV, which is able to detect Internet gateway in the proactive, reactive, and hybrid situation. This evaluation is done by means of simulation using NS-2 developed by University California Berkeley. There are several ad hoc routing protocols, such as AODV, DSR, and DSDV that propose solutions for routing within a mobile ad hoc network. However, since there is an interest in communication between not only mobile devices in an ad hoc network, but also between a mobile device in an ad hoc network and a fixed device in a fixed network (e.g. the Internet), the ad hoc routing protocols need to be modified. In this thesis the ad hoc routing protocol AODV is used and modified to examine the interconnection between a mobile ad hoc network and the Internet. For this purpose Network Simulator 2, NS 2, has been used. Moreover, three proposed approaches for gateway discovery are implemented; propose a forwarding algorithm, and route determination algorithm for default route and host route in MANET are investigated.